2015
DOI: 10.1155/2015/282984
|View full text |Cite
|
Sign up to set email alerts
|

Muscle IGF-1-Induced Skeletal Muscle Hypertrophy Evokes Higher Insulin Sensitivity and Carbohydrate Use as Preferential Energy Substrate

Abstract: We characterized the metabolic profile of transgenic mice exhibiting enhanced muscle mass driven by increased mIGF-1 expression (MLC/mIGF-1). As expected, 6-month-old MLC/mIGF-1 mice were heavier than age-matched wild type (WT) mice (37.4 ± 0.3 versus 31.8 ± 0.6 g, resp.). MLC/mIGF-1 mice had higher respiratory quotient when compared to WT (0.9 ± 0.03 versus 0.74 ± 0.02, resp.) suggesting a preference for carbohydrate as the major fuel source. MLC/mIGF-1 mice had a higher rate of glucose disposal when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
(35 reference statements)
7
13
0
Order By: Relevance
“…Indeed, it has been shown that glucose restriction results in depletion of NAD + and Nampt levels and decreased activity of SIRT1, which was associated with impaired myogenesis (Fulco et al 2008). The increased need for energy to cover anabolic processes is supported by the finding that GLUT4 content was increased in our hypertrophy model, in accordance with findings of earlier studies (Kruger et al 2013;Christoffolete et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, it has been shown that glucose restriction results in depletion of NAD + and Nampt levels and decreased activity of SIRT1, which was associated with impaired myogenesis (Fulco et al 2008). The increased need for energy to cover anabolic processes is supported by the finding that GLUT4 content was increased in our hypertrophy model, in accordance with findings of earlier studies (Kruger et al 2013;Christoffolete et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…18a, b). These physiological alterations, which take place at older ages than the skeletal muscle dysfunctions, recapitulate well those extensively seen in other mouse models with either reduced (in the case of Vav2 L332A/L332A mice) or increased (in the case of Vav2 Onc/Onc mice) skeletal muscle mass 12,13,15,17,18,68,75 . Many dysfunctions found in Vav2 L332A/L332A mice also resemble those found in HFD-fed WT mice (this work), further suggesting that they are caused by the progressive accumulation of body fat indirectly caused by the early alterations in muscle mass and function detected in those mice.…”
Section: E Dsupporting
confidence: 81%
“…This indicates that the preferred fuel in these mice comes from carbohydrate sources rather than from fat. Such a shift in respiratory quotients has been observed in other mouse models with skeletal muscle hypertrophy 15,17 .…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations